To find the first three terms of the arithmetic sequence defined by the given recursive formula, we can calculate \(a_2\) and \(a_3\) using the initial term \(a_1\).
We are given:
- \(a_1 = -5\)
- The recursive formula \(a_n = a_{n-1} + 4\).
Now, let's calculate \(a_2\) and \(a_3\):
-
Calculate \(a_2\): \[ a_2 = a_1 + 4 = -5 + 4 = -1 \]
-
Calculate \(a_3\): \[ a_3 = a_2 + 4 = -1 + 4 = 3 \]
Thus, the first three terms of the sequence are:
- \(a_1 = -5\)
- \(a_2 = -1\)
- \(a_3 = 3\)
So, the results are:
- \(a_1 = -5\)
- \(a_2 = -1\)
- \(a_3 = 3\)